The Key Role of Uric Acid in Oxidative Stress, Inflammation, Fibrosis, Apoptosis, and Immunity in the Pathogenesis of Atrial Fibrillation - Deng, Yawen; Liu, Fei; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2021)
Atrial fibrillation (AF) is a highly prevalent cardiac arrhythmia that leads to numerous adverse outcomes including stroke, heart failure, and death. Hyperuricemia is an important risk factor that contributes to atrium injury and AF, but the underlying molecular mechanism remains to be elucidated. In this review, we discussed the scientific evidence for clarifying the role of hyperuricemia in the pathogenesis of AF. Experimental and Clinical evidence endorse hyperuricemia as an independent risk factor for the incidence of AF. Various in vivo and in vitro investigations showed that hyperuricemia might play a critical role in the pathogenesis of AF at different UA concentrations through the activation of oxidative stress, inflammation, fibrosis, apoptosis, and immunity.